2014
DOI: 10.1186/1757-2215-7-54
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of VEGF and VEGF receptors are associated with the occurrence of ovarian hyperstimulation syndrome (OHSS)—a retrospective case–control study

Abstract: BackgroundOvarian hyperstimulation syndrome (OHSS) is the most serious complication of IVF/ICSI therapy. The pathophysiology and etiology of the disease is still not fully clarified.MethodsTo assess whether polymorphisms of the VEGF/VEGF-receptor system contribute to the occurrence of ovarian hyperstimulation syndrome (OHSS), we performed a retrospective analysis of 116 OHSS patients, and 124 female controls. The following SNPs were genotyped: Rs2071559 (VEGFR2-604); rs2305948 (VEGFR2-1192); rs1870377 (VEGFR2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The severe forms registered tense ascites, hemodynamic instability, renal failure, respiratory distress syndrome, hemorrhage from ovarian rupture, and thromboembolism. Recent data also suggest that hCG increases the expression of VEGF/VEGFR2 in human granulosa cells and raises serum VEGF-A [53]. Pregnant patients with OHSS must be monitored very closely because of the increased risk of deterioration due to the rapidly rising serum concentrations of hCG.…”
Section: Clinical Perspectivesmentioning
confidence: 95%
“…The severe forms registered tense ascites, hemodynamic instability, renal failure, respiratory distress syndrome, hemorrhage from ovarian rupture, and thromboembolism. Recent data also suggest that hCG increases the expression of VEGF/VEGFR2 in human granulosa cells and raises serum VEGF-A [53]. Pregnant patients with OHSS must be monitored very closely because of the increased risk of deterioration due to the rapidly rising serum concentrations of hCG.…”
Section: Clinical Perspectivesmentioning
confidence: 95%
“…OHSS is a self-limiting disorder with a broad spectrum of clinical manifestations related to increased capillary permeability and fluid retention mediated by many inflammatory mediators such as VEGF [21]. hCG treatment increases the production of VEGF in endothelial cells, and the growth factor in turn increases vascular permeability [22].…”
Section: Discussionmentioning
confidence: 99%
“…Nouri and colloquies confirmed that VEGF gene polymorphism is related with the happening of OHSS (13). Even patients with VEGF +405 CC genotype have increased the risk of OHSS (14).…”
Section: Discussionmentioning
confidence: 91%
“…Polymorphisms -460 C/T and +405 G/C are up the regulator and were associated with increased VEGF basal promoter activity and enable to increase permeability (10-12). Polymorphisms in the VEGF gene could be associated with the occurrence of OHSS (13). Increased risk of OHSS was reported in patients with VEGF +405 C/C genotype (14).…”
Section: Introductionmentioning
confidence: 99%